Growth pattern and otolith size of Tor spp. (Cyprinidae) - Khairiza Lubis; Lydia Ruth Hasianna Manullang; Ferosalina Natasia Saragih; Debi Rausana Nasution; Mufti Sudibyo; Elida Hafni Siregar; Agung Setia Batubara (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The threat of decreasing populations of Tor species continues to increase due to intensive fishing, habitat destruction and infrequent cultivation efforts. Monitoring of this group of fish must be carried out routinely to reveal the population conditions of fish. This research aims to reveal the population conditions of fish through an analytical approach to the length-weight relationship and fish otolith size. All fish samples were then taken for otoliths to measure their size and analyzed further using a scanning electron microscope (SEM). The research was conducted in the Tangkahan River, North Sumatra, Indonesia from January-March, 2023. The results showed that 43 samples of T. douronensis, 34 samples of T. tambra, and 24 samples of T. tambroides had b values of 2.853, 2.757, and 2.353, respectively. The b value in this study indicated that the fish had a negative allometric growth pattern. The size of the otoliths of the three Tor species shows that T. tambra has the highest length (the distance measured from the anterior to the posterior of the of sagitta otolith) on average reaching 9.31 mm, while T. tambroides and T. douronensis only reach 1.53 mm and 1.83 mm. The results were confirmed by ANOVA showing significant differences (P 0.05) in the mean value of otolith size based on Tor species, where the otolith size of T. tambra was significantly different compared to the other two species. The condition of Tor species in the Tangkahan River has experienced ecological pressure. This indication was concluded from the results of the analysis of the length-weight relationship of fish which showed b value 3 (negative allometric). The results show that the characteristics and size of the otoliths can differentiate Tor species and facilitate identification efforts related to management and conservation.Keywords:Habitat DestructionNegative AllometricAnterior of Sagitta OtolithPosterior of Sagitta Otolith